MENINGKATKAN KESADARAN KAUM MUDA TERHADAP PERPAJAKAN DI INDONESIA MELALUI PROGRAM SOSIALISASI PAJAK BAGI MAHASISWA FAKULTAS EKONOMI UNIVERSITAS DARMA PERSADA - A. Indriani; Saminem Saminem; E.N. Handayani; Sukardi Sukardi; R. Saprianto (Jurnal Abdimas Bina Bangsa, 2024)
The seminar "Tax Goes to Campus: Evidence of Care for the Country" was specifically designed to enhance tax awareness among students, emphasizing the crucial role of taxes in the development and welfare of the nation. Utilizing a dynamic and interactive approach, it effectively engaged participants, fostering a deeper comprehension of taxation's impact. The initiative's success was underscored by significant improvements in tax knowledge among attendees, as demonstrated by pre and post-evaluation results. This underscores the effectiveness of interactive educational programs in cultivating a responsible tax culture among the youth. The positive outcomes suggest a strong foundation for the development of further educational endeavours aimed at reinforcing tax awareness, highlighting the importance of such programs in educating and preparing the younger generation for their roles as informed citizens in a tax-compliant society